The Children’s Perception toward Comic in Developing Indonesia Children’s Mentality - Hennilawati Hennilawati (Politeknik Negeri Padang, 2018)
The purpose of this research is to see the moral values aspect in child comics by conducting sociology literature. It uses the qualitative method with the data sources are used by 10 comic Naruto. The results of this research are positive aspects of moral value, such as (1) life passion, (2) courage, (3) affection, (4) solidarity, (5) sacrifice, (6) love the homeland.